PROSPEK USAHA PEMBENIHAN IKAN NILA GIFT (Oreochomis nilotikus,sp) DI KABUPATEN NAGAN RAYA PROPINSI ACEH - T. Amarullah; Zuriat Zuriat; Syarifah Zuraidah; Dewi Mustika (Universitas Teuku Umar, 2020)
Fish hatchery is one of the stages in fish farming. Fish hatcheries are carried out in an effort to obtain seed candidates to be marketed in the community fish rearing business. The research was carried out on the Beumaju partner hatchery business in Blang Padang Dalam village with the aim of knowing the income and the feasibility of the gift tilapia hatchery business. The research method uses quantitative descriptive analysis to provide a discussion using calculations on the production which is displayed in tabular form. The results of this study indicate that the business parameters of tilapia hatchery are TC, TR, Profit, R / C Ratio, Playback Period, Break Event Point and Profitability in Blang Dalam Village, Beutong District, Nagan Raya Regency as follows: TC (total cost) ranges from 190,173 .000, TR (revenue) ranged from 3113,950,000, Profit ranged from 123,777,000, R / C Ratio ranged from 1.65, payback period ranged from 1.12 and Break Event Point 724,468 and Rentability ranged from 89.21. The conclusion and result of this research is that the tilapia hatchery business in Blang Dalam Village is feasible to be implemented.